2015
DOI: 10.1590/1981-5794-1502-7
|View full text |Cite
|
Sign up to set email alerts
|

Percepção E Produção Dos Padrões De Vot Do Inglês Por Aprendizes Brasileiros: O Papel De Múltiplas Pistas Acústicas Sob Uma Perspectiva Dinâmica

Abstract: • ABSTRACT: In this study, departing from a dynamic conception of L2 phonetic-phonological acquisition, we investigate 34 Southern Brazilian learners' perception (identification and discrimination) and production of VOT patterns of initial stops in English. We initially hypothesized that, especially among learners with a basic level of L2 proficiency, VOT was not the main acoustic cue employed in the perception of voicing distinctions. Our results show that, regardless of the learners' proficiency level (basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
1
4
0
16
Order By: Relevance
“…The findings in the current study are also in accordance with earlier studies examining L2 English among Arab speakers (Alves & Zimmer, 2015;Buali, 2010;Calvo, 2016;Flege & Port, 1981;Gordon & Darcy, 2016;Khattab, 2002;Port & Mitleb, 1983;Olson, 2017;Olson & Hayes-Harb, 2019;Rato & Rauber, 2015). In these studies, it was reported that all Arab L2 speakers are able to distinguish between the English voiced /b/ and the aspirated voiceless /p/, although this contrast does not exist in their L1 (Arabic).…”
Section: Maintenance Of the English Stop Voicing Contrast By Arab L2 supporting
confidence: 92%
“…The findings in the current study are also in accordance with earlier studies examining L2 English among Arab speakers (Alves & Zimmer, 2015;Buali, 2010;Calvo, 2016;Flege & Port, 1981;Gordon & Darcy, 2016;Khattab, 2002;Port & Mitleb, 1983;Olson, 2017;Olson & Hayes-Harb, 2019;Rato & Rauber, 2015). In these studies, it was reported that all Arab L2 speakers are able to distinguish between the English voiced /b/ and the aspirated voiceless /p/, although this contrast does not exist in their L1 (Arabic).…”
Section: Maintenance Of the English Stop Voicing Contrast By Arab L2 supporting
confidence: 92%
“…CristófaroSilva et al (2019) listed VOT values for voiceless plosives in BP, which were obtained in several works, showing a great variation in values: [p] 11 ms -37.67 ms; [t]: 15 ms -36.52 ms and [k]: 35 ms -58.05 ms. Recent works showed an emergent aspiration in voiceless plosives in BP(Alves and Zimmer 2015;Kupske 2017). Furthermore, none of the works mentioned above refer to the BP variety reported in this paper.…”
mentioning
confidence: 66%
“…In tandem with investigations on L2 production, the number of perceptual studies have also increased considerably in the Brazilian scenario. Still regarding final stops in English, Albuquerque 2012 2014and Alves and Zimmer (2015) showed that VOT is not the main acoustic cue employed by Brazilian learners in the identification and discrimination of minimal pairs such as 'pat-bat', and that a multitude of cues might be at play in L2 perception. This, once again, conforms to the dynamic theoretical perspective according to which language development emerges from the interaction of a multitude of factors.…”
Section: L2 Pronunciation Research In Brazil: a Dynamic Accountmentioning
confidence: 99%